Application of experience gleaned from the WHL system in national heritage protection systems – opportunities and benefits - Bogusław Szmygin (Ochrona Dziedzictwa Kulturowego, 2023)
As part of the UNESCO World Heritage System, a unique methodology for the analysis of cultural properties and standards for their protection and management have been developed. The protection of UNESCO properties should be carried out in accordance with these standards. However, the protection of cultural property inscribed on the World Heritage List is carried out within the framework of national monument protection systems. Meanwhile, the standards, methodologies and procedures in force in the World Heritage system, developed by international experts, are in many respects not inconsistent with national heritage protection systems. Therefore, it is necessary to postulate the inclusion of the World Heritage methodology in national heritage protection systems. This is justified for two reasons – it will facilitate the protection of UNESCO properties in accordance with established standards, and it will improve the quality of national heritage protection systems.